Prevalência de diabetes mellitus diagnosticado na gravidez e fatores associados: estudo observacional - Figuerêdo, Luana Machado (2023)
Introduction: The prevalence of Diabetes Mellitus(DM) diagnosed during pregnancy has been increasing in Brazil and worldwide. It is conceptually divided into: Gestational Diabetes Mellitus(GDM) and DM Franco recognized in Pregnancy (Overt Diabetes). Severalrisk factorsare known, but the association with hypovitaminosis D has been investigated. Objective: To assess the prevalence of DM diagnosed during pregnancy as well as its associated factors and its relation to hypovitaminosis D in puerperal women admitted to a maternity hospital in Feirade Santana-BA. Methods: This was an observational, cross-sectional, unicentric, quantitative study. The population consisted of puerperal women hospitalized in the obstetric wards of the HospitalEstadual daCriança in Feira de Santana-BA, who gave birth at the institution, totaling 311 interviewed in the periodbetween November/2022 and August/2023. Data collection included the application of a structured survey, consultation of computerized medical records and prenatal examinations. The diagnosis of DM during pregnancy was defined by fasting glucose and/or a 75g oral glucose tolerance test. In addition, the participants' serum 25- Hydroxy-Vitamin D (25-OH-Vit D) was measured. Results: The prevalence of DM diagnosedin pregnancy was 22.22%, of which 16.8% were GDM and 5.38% Overt Diabetes. A previoushistory of DM in former pregnancies was associated with the diagnosis of DM during pregnancyamong the puerperal women interviewed [OR 4.9 and p = 0,04]. Pre-pregnancy Body Mass Index (BMI) > 29.9kg/m2 also showed a statistically significant association with the diagnosisof DM during pregnancy [OR 2.55 and p<0.0001]. The median serum levels of 25-OH-Vit D did not differ significantly in women with and without DM diagnosed during pregnancy, respectively 27.0 [21.5-32.3] and 26.7 [21.5-32.4], p = 0.795. Conclusions: The prevalence ofDM diagnosed during pregnancy in this study was higher than the estimated prevalence in Brazil and worldwide. Regarding the associated factors investigated, a history of DM in previous pregnancies and being overweight were associated with the occurrence of DM duringpregnancy. However, no association with hypovitaminosis D was confirmed.